2020
DOI: 10.2196/21875
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Usage Among Urologists During the COVID-19 Pandemic: Cross-Sectional Study

Abstract: Background Prior to the COVID-19 pandemic, urology was one of the specialties with the lowest rates of telemedicine and videoconferencing use. Common barriers to the implementation of telemedicine included a lack of technological literacy, concerns with reimbursement, and resistance to changes in the workplace. In response to the COVID-19 pandemic declared in March 2020, the delivery of urological services globally has quickly shifted to telemedicine to account for the mass clinical, procedural, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
1
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 18 publications
1
73
1
3
Order By: Relevance
“…A study by Dubin et al revelaed increased use of telemedicine by urologists, with the majority of the urologists declaring they wanted to continue using it in their routine practice. 22 Although, our results showed a lower ratio of preference of telemedicine in Turkey, it seems a gradual increase day by day. This fact was supported by the survey that evaluated patients' perspective for telemedicine during pandemic and showed that majority of the patients wished for telemedicine(84.7%) rather than clinical visits.…”
Section: Discussioncontrasting
confidence: 53%
“…A study by Dubin et al revelaed increased use of telemedicine by urologists, with the majority of the urologists declaring they wanted to continue using it in their routine practice. 22 Although, our results showed a lower ratio of preference of telemedicine in Turkey, it seems a gradual increase day by day. This fact was supported by the survey that evaluated patients' perspective for telemedicine during pandemic and showed that majority of the patients wished for telemedicine(84.7%) rather than clinical visits.…”
Section: Discussioncontrasting
confidence: 53%
“…Although earlier studies in the US have paid attention to the wide variation in telehealth use by specialty, the aforementioned study was the first to quantify the variation across medical specialties at the individual provider level. The results of this landmark 2018 study have already been widely referenced in the general telehealth literature, and the evidence has been corroborated in the growing ‘specialty-level’ telehealth literature during the pandemic [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 55%
“…Dubin et al . [ 7 ] find lack of technological comprehension, patients´ lack of access to required technology, and reimbursement concerns to be the main barriers to use telemedicine. Perhaps these reasons apply in Tunisia.…”
Section: Discussionmentioning
confidence: 99%